A new marine clupeoid fish from the Lower Cretaceous of the Sergipe-Alagoas Basin, northeastern Brazil - de Figueiredo, Francisco J. (Zootaxa, 2009)
Clupeomorph fishes are largely diversified and widespread in Cretaceous strata of northeastern Brazil. They are represented by basal clupeiforms, †ellimmichthyiforms, and advanced clupeoids. In this paper, a new clupeoid fish, †Nolfia riachuelensis sp. nov., is described based on a specimen found in marine shale yielded in the Taquari Member (Albian) of Riachuelo Formation, Sergipe-Alagoas Basin. Although partially preserved (most of skull is lacking), the fish shows many informative characters, particularly in the axial skeleton. The fish is morphologically very similar to †Nolfia kwangoensis, a clupeoid fish originally described from marine deposit from the Upper Cretaceous (Cenomanian) of Kipala, Democratic Republic of Congo, with which it shares: 18 caudal vertebrae; long and cylindrical pleural ribs; posteriormost pleural ribs supported by long parapophyses and gradually decreasing in size posteriorly; very reduced ural centra; presence of long and distally congruent neural spines of third, second, and first preural centra; three uroneural bones (the first probably forming the pleurostyle). Otherwise, †Nolfia riachuelensis sp. nov. differs from other clupeomorphs by a unique combination of features. The number of supraneural bones, aligned rod-like postcleithra, less than 30 rays in the anal fin, and derived absence of dorsal scutes indicate its placement within Clupeidae. As far as is known, †Nolfia riachuelensis sp. nov. is the most ancient clupeoid fish known from the fossil record.